Korelasi Nilai SPF dan Aktivitas Antioksidan Fraksi Etil Asetat Daun Bandotan (Ageratum conyzoides L.) - Muhammad Fakhawarizmi; Danang Raharjo (Jurnal Kesehatan Amanah, 2026)
Indonesia, as a tropical country, has high ultraviolet (UV) radiation intensity, which increases the risk of skin damage due to oxidative stress. This study aimed to determine the correlation between Sun Protection Factor (SPF) values and antioxidant capacity of the ethyl acetate fraction from bandotan leaves (Ageratum conyzoides L.). The study involved extraction by maceration using 96% ethanol, liquid-liquid fractionation, phytochemical screening, antioxidant activity testing using the ABTS method, and SPF value determination by UV-Vis spectrophotometry. The results showed that the ethyl acetate fraction exhibited the highest antioxidant activity with an IC₅₀ value of 21.726 ppm (very strong category) and the highest SPF value of 23.28 (ultra protection category). Statistical analysis indicated a significant positive correlation between antioxidant capacity and SPF values, with a correlation coefficient (R) of 0.647 and a coefficient of determination (R²) of 0.418 (p < 0.05). This study demonstrates that the ethyl acetate fraction of bandotan leaves has potential to be developed as a natural sunscreen ingredient with high antioxidant activity.